SAT0168 Discontinuation of first biologic therapy in rheumatoid arthritis: main causes and correlation between secondary inefficacy and development of immunogenicity. (15th June 2017) - Bogas, P; Plasencia, C; Pascual-Salcedo, D; Bonilla, G; Moral, E; Tornero, C; Nuño, L; Villalba, A; Peiteado, D; Martinez, A; Hernandez, B; Balsa, A
Abstract : Background: Biologic therapy has been a major change in Rheumatoid Arthritis (RA) prognosis, but around 40% of patients (pts) fail to respond. Part of this treatment failure can be explained by the development of anti-drug antibodies (ADA), but the ADA-associated secondary inefficacies rate is currently unclear Objectives: To assess in our AR cohort treated with Adalimumab (Ada), Infliximab (Ifx), etanercept (Etn), certolizumab (Czp), Tocilizumab (Tcz) and Abatacept (Abt) as 1st biologic agent, the frequency of drug suspension as well as the main causes for discontinuation and the secondary inefficacy rate associated with the development of immunogenicity Methods: From the RA cohort that initiated their 1st biologic agent at Hospital La Paz between 2005 and 2016, only those who had suspended those drugs were included, and causes for suspension were collected. Clinical activity was measured by DAS28 and Delta-DAS28 at 6 months of treatment to classify discontinuation by primary or secondary inefficacy. Drug levels (DL) and/or ADA were also measured by ELISA at 6 months since initiating the biologic agent in 43 pts and at drug discontinuation in 59 pts. Primary inefficacy was defined as DAS28>3.2 and delta-DAS28 <1.2 at 6 months with DL present. Secondary inefficacy was defined both as DAS28>3.2 plus delta-DAS28 <1.2 at 6 months with ADA+ and Delta-DAS28>1.2 or DAS28 <3.2 at 6 months with subsequent loss of efficacy. Statistical analysis was performed using SPSS version 20.0 Results: From the 246 pts who started their first biologic therapy, 144 (58%) pts who had definitively discontinued were included. [Ifx (n 35, 24%), Ada (n 40, 28%), Etn (n 30, 21%), Czp (n 23, 16%), Tcz (n 10, 7%) y Abt (n 6, 4%)]. 116 (80, 6%) were women. The mean age was 56.3±14.7 years. The mean time of biologic was 2.23±1.96 years. From the global cohort, 18 (12.5%) drop out the treatment due to primary inefficacy, 41 (28.5%) to secondary inefficacy, 57 (39.6%) to adverse effects (AE), 11 (7.6%) to remission and 17 (11.8%) to other causes (surgery, pregnancy, etc.). 12.5% pts who discontinued due to AE or other causes had also a primary or secondary inefficacy; by including those pts in these last causes for suspension, a total of 20 pts (14%) failed due to primary inefficacy and 57 pts (39.6%) to secondary inefficacy. The most frequent AEs were: infections (35%), cutaneous AEs (psoriasis, rash, etc. (10.5%), infusion reactions (9%) and neoplasia (9%). Of the 59 pts who had DL/ADA measured at drug discontinuation, 42.4% were ADA +. Within the group that failed due to secondary inefficacy and had DL/ADA determined, 50% were ADA+; nevertheless this rate was smaller in suspensions due to other causes. Likewise, in the ADA+ pts, 73% suspended due to secondary inefficacy Conclusions: In our RA cohort, adverse effects were the main cause for discontinuation, with infections at 1st place. The 2nd cause conditioning interruption was the secondary inefficacy, in which 50% of our pts were ADA+ at drug discontinuation. These data suggest that the development of ADA is a frequent cause of secondary inefficacy in our RA pts Disclosure of Interest: None declared